Shiʻi cosmopolitanisms in Africa : Lebanese migration and religious conversion in Senegal - Leichtman, Mara (Public cultures of the Middle East and North Africa., 2015)
Mara A. Leichtman offers an in-depth study of Shi'i Islam in two very different communities in Senegal: the well-established Lebanese diaspora and Senegalese "converts" from Sunni to Shi'i Islam of recent decades. Sharing a minority religious status in a predominantly Sunni Muslim country, each group is cosmopolitan in its own way. Leichtman provides new insights into the everyday lives of Shi'i Muslims in Africa and the dynamics of local and global Islam. She explores the influence of Hizbullah and Islamic reformist movements, and offers a corrective to prevailing views of Sunni-Shi'i hostility, demonstrating that religious coexistence is possible in a context such as Senegal.